2016
DOI: 10.1108/jcm-01-2015-1281
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of online review deceptions: an empirical study in China

Abstract: Purpose To influence consumer perceptions, firms often manipulate online product reviews on their own websites or third-party forums by anonymously adding positive reviews, deleting unfavorable reviews or offering rewards to encourage favorable reviews. This study aims to investigate consumer perceptions of online review deceptions and how these perceptions influence their subsequent purchase behavior. In particular, consumers’ awareness, suspicion and detection are studied and specific manipulation tactics ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 49 publications
3
76
0
1
Order By: Relevance
“…This keyword-based sentiment analysis, although reduces the volume of reviews, could have its flaws in the form of wrong interpretation or incomplete feedback. There could be more trials to ameliorate this challenge to avoid mistrust in reviews as shown by some respondents in (Jin Ma and Lee, 2014;Peng et. al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This keyword-based sentiment analysis, although reduces the volume of reviews, could have its flaws in the form of wrong interpretation or incomplete feedback. There could be more trials to ameliorate this challenge to avoid mistrust in reviews as shown by some respondents in (Jin Ma and Lee, 2014;Peng et. al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies into these challenges have been investigated as follows: information quality (Lee et al, 2008;Blooma et al, 2012;Yagci and Das, 2018), sentiments (Brody and Elhadad, 2010; Yang and Chao, 2018), exaggerations (Baker and Kim, 2019), manipulations (Jin Ma and Lee, 2014;Peng et al, 2016).…”
Section: Quality and Reliability Of Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…offering cashback in exchange of favorable reviews, Li and Li, 2016) or "crook" (e.g. falsifying JHTI 4,1 positive reviews, deleting unfavorable reviews and harassing customers who left negative feedback, Peng et al, 2016). Platform business models that tie business sales with platform commissions may be responsible for inducing some of the above practices (Schoenm€ uller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mevcut araştırmanın temel motivasyonu günümüzde çevrimiçi tüketici yorumlarının her geçen gün inandırıcılığını yitirmesi ve çevrimiçi tüketici yorumlarına yönelik şüphelerin artmasıdır. Artık web sitelerinde çevrimiçi tüketici yorumlarının manipüle edildiği, olumlu yorumların ön plana çıkarıldığı, olumsuz yorumların yorum sitelerinden silindiği bilinen bir gerçek haline gelmiştir (Peng, Cui, Zhuang ve Li, 2016). Böyle bir ortamda çevrimiçi tüketici yorumlarının inandırıcılığını arttırmak, gerçek kullanıcılar tarafından yazıldığını vurgulamak ve bu yorumları okuyucular için faydalı hale getirmek firmalar için ihtiyaç haline gelmiş; araştırmacılar tarafından ise bu konuların incelenmesi önem kazanmıştır.…”
Section: Introductionunclassified